ANALYSIS OF EDUCATIONAL VALUE IN THE DRAMA GONG SAMPIK ENGTAY BY ISI DENPASAR STUDENTS - Ida Ayu Gede Sasrani Widyastuti; Dewa Gede Satya Adi Maha Utamia (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2025)
This study aims to analyze the educational values embedded in the performance of the drama gong Sampik Engtay by students of the ISI Denpasar Performing Arts Education Study Program. The research focuses on the moral, social, cultural, and character-building values that emerge through the performance. The study employs a qualitative method with a symbolic interactionism approach, utilizing data collection techniques such as observation, in-depth interviews, and literature reviews. The analysis is conducted using Erving Goffman’s Dramaturgy Theory and George Herbert Mead’s Self-Concept, which explore identity formation, role-playing, and social interaction within the context of performing arts. The findings indicate that Sampik Engtay conveys significant educational values, including moral integrity, perseverance, and cultural appreciation. These values are reflected in the depiction of identity conflicts, personal sacrifices, and the struggle of individuals in adhering to social norms. Additionally, the performance serves as a medium for reinforcing students' understanding of ethical principles, social responsibility, and the importance of preserving cultural heritage. The research highlights the role of traditional drama gong as an effective tool for education, fostering cultural appreciation, and strengthening the character of students. Furthermore, this study provides valuable insights for educators, performing arts practitioners, and policymakers in integrating performing arts into the educational curriculum and preserving Balinese traditional performances for future generations.